The hobbit, or, there and back again - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. (London : HarperCollinsPublishers, 2012)
Bilbo Baggins, a respectable, well-to-do hobbit, lives comfortably in his hobbit-hole until the day the wandering wizard Gandalf chooses him to take part in an adventure from which he may never return.
Keywords: Baggins, Bilbo (Fictitious character) -- Fiction; Wizards -- Fiction; Dwarfs -- Fiction; Dragons -- Fiction; Middle Earth (Imaginary place) -- Fiction